Effects of Lewis number on heat and mass transfer in a triangular cavity - Hasanuzzaman, M.; Rahman, M. M.; Öztop, Hakan Fehmi; Rahim, N. A.; Saidur, R. (Pergamon-Elsevier Science Ltd, 2012)
The double-diffusive mixed convection in a right triangular is analyzed by solving the mass, momentum, energy and concentration balance equations. The flow is considered to operate in the laminar regime under steady state conditions. Moreover, Galerkin weighted residuals finite element method is applied to solve the governing equations. The study is performed for different values of Lewis number, Richardson number and the direction of the sliding wall motion. Heat and mass transfer characteristics as streamlines, isotherms, isoconcentration lines, average Nusselt and Sherwood numbers are studied for the aforesaid parameters. It is found that heat transfer decreased by 3.6% and 3.7% as Le increases from 5 to 20 at Ri = 5 for cases 1 and 2 respectively. On the other hand, at the same convective regime, mass transfer rate increased by 32.4% and 38.4% as Le increases from 5 to 20. for cases 1 and 2 respectively. Moreover, the flow, temperature and concentration fields are controlled by the direction of the sliding wall. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Double-diffusive; Mixed convection; Triangular cavity; Sliding wall